2017
DOI: 10.1021/acsomega.7b01102
|View full text |Cite
|
Sign up to set email alerts
|

Octanol–Water Partition Coefficient Measurement by a Simple 1H NMR Method

Abstract: We describe a simple miniature shake-flask method to measure the octanol–water partition coefficient of an organic compound. Partition between water and octanol is performed in an NMR tube; the aqueous phase is analyzed by 1 H NMR spectroscopy using a benchtop low-field NMR instrument. Neither pre-equilibration of solvents nor isolation of the two phases is required. The procedure is fast and easy enough to be used in a students’ laboratory. Scope and limitations as well as possible sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 20 publications
6
78
0
4
Order By: Relevance
“…It distributes uniformly with body water (USEPA, 2003). As a semipolar solvent, acetone has a relatively low octanol-water partition coefficient (0.58), and consequently has a limited potential for sequestration in fat (Cumming & Rucker, 2017). The relative role of hepatic metabolism (with shunting into glucose pathways) vs. excretion of the native compound (in exhaled breath > urine) is dependent both on individual physiology and dose rate (USEPA, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…It distributes uniformly with body water (USEPA, 2003). As a semipolar solvent, acetone has a relatively low octanol-water partition coefficient (0.58), and consequently has a limited potential for sequestration in fat (Cumming & Rucker, 2017). The relative role of hepatic metabolism (with shunting into glucose pathways) vs. excretion of the native compound (in exhaled breath > urine) is dependent both on individual physiology and dose rate (USEPA, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative nuclear magnetic resonance (qNMR), typically using the proton nucleon with its high abundance and unitary signal response, has found use across a wide array of important applications . This includes the use of qNMR to determine partition coefficients . When using 1 H NMR spectroscopy, analytes do not need to be UV‐active, and narrow linewidths mean that signals belonging to the same or different compounds that lie within a few Hz of each other can be fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we demonstrated that a combination of 1 H NMR spectroscopy and CRAFT data analysis could be used to accurately determine partition and distribution coefficients for a variety of analytes . Similar to the approaches of Cumming et al and Mo et al, quantitation was performed in the presence of water and 1‐octanol solvent signals requiring that the receiver gain be set to zero. An internal standard was not required because signal amplitudes were measured at the same receiver gain value and the resulting partition coefficient is a ratio of signal amplitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other applications of log K ow are in liquid chromatography [3][4][5], liquid-liquid extraction [6], solid-phase extraction [7] and solid-phase microextraction [8,9]. Common values for log K ow are reported as obtained from experimental determinations [10][11][12][13][14][15][16][17][18][19]. Values for log K ow are also obtained based on various types of estimations [20][21][22][23][24][25][26][27][28][29], and several computer packages allow the calculation of the values for log K ow [http://www.epa.gov/oppt/exposure/pubs/episuite.htm], [http://www.chemaxon.com], [http://logkow.cisti.nrc.ca/logkow/search.html].…”
Section: Introductionmentioning
confidence: 99%